Epidemiological trends of acute coronary syndrome in Shimla district of the hilly state of Northern India: Six-year data from the prospective Himachal Pradesh acute coronary syndrome registry - Chand Negi, Prakash (Indian Heart J, 2019)
OBJECTIVES: The epidemiological trends of incidence, treatment practices, and outcomes are reported from Shimla district of the northern state of India. METHODS: The data of clinical characteristics, treatment practices, and outcomes of patients with acute coronary syndrome (ACS) diagnosed using standard criteria were collected systematically from the defined hilly geographical region of the northern state of India from January 2013 to December 2018 as the part of Himachal Pradesh acute coronary syndrome (HP ACS) registry. The year-wise trends of incidence, demographic, clinical characteristics, treatment practices, and in-hospital mortality are reported. RESULTS: The incidence of ACS shows declining trends. The mean age at incident ACS is increasing without change in gender predilection. The prevalence of overweight/obesity and diabetes has increased significantly since 2013 but tobacco consumption has not changed. The reperfusion therapy has increased significantly (20.9% in 2013 to 42.1% in 2018, p < 0.01) primarily because of an increased use of percutaneous coronary angioplasty. There is a trend of increasing use of beta blockers. The use of other oral secondary preventive drugs remained more than 90% since 2013. The in-hospital mortality rate is declining (9.0% in 2013 to 6.0% in 2018, p < 0.01). CONCLUSIONS: Epidemiological characteristics of the ACS population in Shimla district are changing. The trends of use of reperfusion therapy in ST segment elevated myocardial infarction population has although increased but is still suboptimal, and there is a need for taking initiatives both at the system and population level to improve the reperfusion therapy.